PSIKOLOGI ISLAMI (Sebuah Pendekatan Alternatif Terhadap Teori-teori Psikologi) - muhtar Gojali (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2016)
Secular psychology has undergone an out of ideas in understanding the attitude and the uniqueness of human being. According to this psychology, all of human attitudes stand on physical-psychological, educational, and social-cultural dimentions, so that it is not able to answer the deepest aspect of transcendent human attitudes. Islamic psychology offers an integral concept based on revelation on the uniqueness of human being by studying the structure of man, namely what we called latha’if consist of nafs, qalb, aql, and ruh. These four components moved various potentials of man. Therefore, without abolishing the discoveries of seculer psychology, the perception of Islamic psychology was built based on Quranic verses, painted in the universe (afaq) and written in the human itself (nafsani). Islamic psychology has to be seen as an effort to open the sacret of divine laws (sunnatullah) in the human being itself (nafsani verses), to study and to discover various pillars, elements, processes, functions and laws on the psychological aspects of human being.